Analisis Geoteknik Degradasi Fondasi Bangunan Pesisir Lhokseumawe: Integrasi Dinamika Siklus Hidrologi, Fluktuasi Muka Air Tanah, dan Intrusi Air Laut - Lusyana Eka Wardani; Aisyah Protonia Tanjung (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Groundwater level fluctuations are a significant geotechnical factor influencing the stability and integrity of building foundations, particularly in coastal areas affected by seasonal hydrological cycle dynamics, tidal variations, and seawater intrusion. Lhokseumawe City, as an industrial and coastal residential area in North Aceh, is characterized by geological conditions dominated by water-saturated alluvial soils with low permeability, making it vulnerable to pore water pressure fluctuations, reductions in soil bearing capacity, and the risk of progressive subsidence. This study employs a systematic literature review method with an in-depth analysis of 22 national and international scientific references published between 2020 and 2025, obtained from ScienceDirect, SpringerLink, Scopus, and national engineering journal repositories. The review focuses on: (1) the relationship between seasonal rainfall patterns, tidal processes, and groundwater level fluctuations; (2) the quantitative impacts of groundwater level rise and decline on effective stress, foundation bearing capacity, and structural deformation; and (3) the mechanisms of seawater intrusion and its effects on reinforcement corrosion and concrete degradation in reinforced foundations. The synthesis results indicate that groundwater level rise due to extreme rainfall and high tides can increase pore water pressure by up to 20–30 kPa, reduce soil shear strength by approximately 35–40%, and decrease the bearing capacity of shallow foundations by 30–50%. Conversely, groundwater level decline resulting from excessive extraction induces clay soil consolidation with potential local subsidence of 1–3 cm/year, differential settlement, and structural damage in buildings that have been in service for several decades. Furthermore, seawater intrusion increases groundwater salinity, with chloride concentrations reaching 2,000–5,000 mg/L in coastal zones, thereby accelerating reinforcement depassivation and corrosion in reinforced foundations. These findings underscore the importance of adaptive foundation design, groundwater extraction control, and integrated seawater intrusion mitigation strategies to support the sustainability of coastal infrastructure in Lhokseumawe.